Two-dimensional vertical structure Ti2CTx MXene electrode material and preparation method and application thereof

By preparing a two-dimensional vertical structure Ti2CTx MXene electrode material using melting treatment and electroetching methods on flexible carbon fabrics, the electrode performance deterioration and environmental pollution caused by HF etching in the prior art was solved, and electrode materials with high conductivity and fast ion transport were achieved.

CN119889940APending Publication Date: 2025-04-25刘铭赫
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411869140.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing MXene electrode materials use HF etchant when etching at room temperature, resulting in deterioration of electrode performance and environmental pollution, while the disorderly arrangement of nanosheets and spontaneous accumulation of spontaneously limiting ion shuttle and transmission.

Method used

A two-dimensional vertical structure Ti2CTx MXene electrode material was prepared on flexible carbon fabrics by melting treatment and electroetching. The use of HF was avoided by constant voltage electrochemical etching, and Ti2CTx with -Cl, -O and -OH terminal groups were generated.

Benefits of technology

The electrode material with good conductivity, low diffusion resistance, fast electron transfer, and deep electrolyte ions penetration are achieved, which avoids the influence of the adhesive on the internal resistance of the electrode material, speeds up the ion movement speed, and improves the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889940A_ABST
    Figure CN119889940A_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional vertical structure Ti2CTx MXene electrode material as well as a preparation method and application thereof, and relates to the technical field of two-dimensional electrode materials. The preparation method comprises the following steps: mixing mixed metal powder consisting of Ti powder and Al powder, molten salt and carbon cloth, carrying out melting treatment to obtain an MAX material based on the carbon cloth, and carrying out electric etching on the material to obtain a Ti2CTx MXene electrode material with a two-dimensional vertical structure; wherein the etching voltage of the electric etching is 0.4-0.8 V, the etching solution is an HCl aqueous solution, the concentration of the etching solution is 1-4M, and the etching time is 1-4d. According to the preparation method, a simple, economical and efficient electric etching method is adopted, the oriented vertical growth MXene nanosheet is directly prepared on the flexible carbon fabric, the influence of a binder on the internal resistance of the electrode material is avoided, and the prepared electrode material has the advantages of being good in conductivity, low in diffusion resistance, fast in electron transmission, deep in electrolyte ion penetration and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of two-dimensional electrode materials, in particular to a two-dimensional vertical structure Ti2CT x MXene electrode materials, preparation methods and applications thereof. Background Art

[0002] As an electrode material, MXene not only has the advantages of traditional two-dimensional structural materials, but also has ultra-high conductivity. The transition metal elements in its layer undergo redox reactions with ions in the electrolyte, thereby compensating for the limitations of double-layer energy storage carbon-based materials in terms of maximum capacitance due to limited surface area, allowing it to obtain more capacitance.

[0003] Most MAX phases can be etched by HF at room temperature, but the etching of MAX phases by HF etchant will form MXenes with -F as the surface termination group, which will lead to the deterioration of electrode device performance and cause environmental pollution. Although the 2D structure of MXene is conducive to increasing the energy storage capacity of supercapacitors, the disordered arrangement and spontaneous restacking of MXene nanosheets prevent ions from directly inserting into the interlayer spacing on the cross section. Constructing a MXene directional vertical layered distribution structure can directly meet ion shuttling and shorten the ion transmission path. Therefore, it is particularly important to seek a green, safe and simple to synthesize electrode material with excellent etching performance. Summary of the invention

[0004] The purpose of the present invention is to provide a two-dimensional vertical structure Ti2CT x MXene electrode materials and their preparation methods and applications are used to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] The present invention provides a two-dimensional vertical structure Ti2CT x The preparation method of MXene electrode material comprises the following steps:

[0007] After mixing the mixed metal powder, molten salt and carbon cloth, the carbon cloth-based MAX material, i.e. Ti2AlC@CF, is obtained by melting.

[0008] The Ti2AlC@CF was electroetched to obtain a two-dimensional vertical structure Ti2CT x MXene electrode material, namely Ti2CT x @CF;

[0009] The mixed metal powder is a mixed metal powder composed of Ti powder and Al powder; preferably, the molar ratio of the Ti powder to the Al powder is 3:1; and the mass ratio of the mixed metal powder to the molten salt is 35 mg:116 mg.

[0010] Furthermore, the molten salt is preferably a mixture of KCl and NaCl in a molar ratio of 1:1.

[0011] Furthermore, the melting treatment is carried out at a temperature of 1000° C. and for a time of 2 hours.

[0012] Furthermore, the etching voltage of the electric etching is 0.4-0.8V, the etching solution is HCl aqueous solution, the etching solution concentration is 1-4M, and the etching time is 1-4d.

[0013] Furthermore, the etching voltage is 0.6V, the etching solution is HCl aqueous solution, the etching solution concentration is 2M, and the etching time is 2d.

[0014] Furthermore, the melting treatment further includes washing and drying steps.

[0015] The present invention also provides the above-mentioned two-dimensional vertical structure Ti2CT x Application of MXene electrode materials as supercapacitor electrode materials.

[0016] Furthermore, the supercapacitor is a zinc ion supercapacitor.

[0017] Furthermore, the electrolyte of the zinc ion supercapacitor is a ZnSO4 aqueous solution.

[0018] The present invention further provides a supercapacitor using the above two-dimensional vertical structure Ti2CT x MXene electrode materials are used as electrode materials.

[0019] Furthermore, the supercapacitor is a zinc ion supercapacitor, the counter electrode is Zn@Cu@CF, and the preparation method of Zn@Cu@CF comprises the following steps:

[0020] A first electrodeposition is performed using carbon cloth as a working electrode, a copper sheet as a counter electrode, and a copper sulfate solution as a plating solution. A second electrodeposition is performed using the first electrodeposited material as a working electrode, a zinc sheet as a counter electrode, and a zinc sulfate solution as a plating solution. The second electrodeposited material obtained is the Zn@Cu@CF.

[0021] The present invention discloses the following technical effects:

[0022] (1) The electrode material of the present invention is a two-dimensional nanostructured material that is directly grown on a conductive substrate without using a binder. The electrode prepared by this method has the advantages of good conductivity, low diffusion resistance, fast electron transmission, and deep electrolyte ion penetration.

[0023] (2) The present invention adopts a simple and cost-effective electro-etching method to directly prepare oriented vertically grown MXene nanosheets on flexible carbon fabrics. These nanosheets can be directly used as electrodes. Compared with electrodes prepared by the coating method, the electrode material prepared by the method of the present invention does not require the use of a binder, thereby avoiding the influence of the binder on the internal resistance of the electrode material. The electrode prepared by this method has the advantages of good conductivity, low diffusion resistance, fast electron transmission, and deep electrolyte ion penetration.

[0024] (3) The present invention increases the interlayer spacing between MXene nanosheets, which determines the dynamics of ion shuttling. A larger interlayer spacing can accelerate the speed of ion movement, thereby facilitating the rapid embedding / de-embedding of ions.

[0025] (4) The present invention uses a constant voltage to electrochemically etch the Ti2AlC MAX phase. This method does not involve any -F, avoids the harm of the traditional HF etching method to the environment and human body, and generates Ti2CT with only -Cl, -O and -OH terminal groups. x .

[0026] (5) High specific surface area Ti2CT of the present invention x MXene combined with flexible carbon fabric substrates offers promising application prospects for high-energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 The two-dimensional vertical structure Ti2CT x MXene electrode material (Ti2CT x @CF) preparation and zinc ion supercapacitor assembly (Ti2CT x Schematic diagram of the @CF / / Zn@Cu@CF HSC) process.

[0029] Figure 2 This is a diagram of the internal reaction mechanism for preparing MXene in the present invention.

[0030] Figure 3The SEM images and EDS images of the MAX prepared in Example 1 of the present invention and the samples etched for different times at a voltage of 0.6 V and a concentration of 2M HCl: (a) SEM image of MAX; (b) SEM image of E-0.6V-2M-1d (2000 times); (c) SEM image of E-0.6V-2M-2d (2000 times); (d) SEM image of E-0.6V-2M-2d (4000 times); (e) SEM image of E-0.6V-2M-2d (60 000 times); (f) SEM image of E-0.6V-2M-4d (2000 times); (g) full spectrum of E-0.6V-2M-2d; (g1) is the EDS element mapping image of O of E-0.6V-2M-2d; (g2) is the EDS element mapping image of C of E-0.6V-2M-2d; (g3) is the EDS element mapping image of Ti of E-0.6V-2M-2d.

[0031] Figure 4 Ti2CT x Elastic recovery performance of @CF electrode material (E-0.6V-2M-2d): (a) C-shaped Ti2CT x @CF electrode material; (b) curved S-shaped Ti2CT x @CF electrode material; (c) unfolded Ti2CT x @CF electrode material.

[0032] Figure 5 XRD patterns of MAX and MXene prepared in Example 1 of the present invention: (a) is the XRD pattern of MAX (Ti2AlC@CF) and E-0.6V-2M-2d (Ti2AlC@CF); (b) is the XRD pattern of E-0.6V-2M-1d, E-0.6V-2M-2d and E-0.6V-2M-4d.

[0033] Figure 6 Ti2CT prepared in Example 1 of the present invention x Infrared spectrum of @CF(E-0.6V-2M-2d).

[0034] Figure 7 XPS spectra of “E-0.6V-2M-2d” prepared in Example 1 of the present invention: (a) overall spectrum of “E-0.6V-2M-2d”, (b) C 1s spectrum; (c) Ti 2p spectrum; (d) O 1s spectrum.

[0035] Figure 8 Ti2CT under different etching voltages x @CF electrochemical performance test: (a)-(c) CV curves; (d)-(f) GCD curves.

[0036] Fig. 9 Ti2CT under different etching voltages x @CF electrochemical performance test: (a) voltage and capacitance at different current densities; (b) EIS curve.

[0037] Fig.10 Ti2CT under different etching solution concentrations x Electrochemical performance test of @CF: (a)-(c) CV curves; (d)-(f) GCD curves.

[0038] Fig.11 Ti2CT with different etching solution concentrations x Electrochemical performance test of @CF: (a) voltage and capacitance at different current densities; (b) EIS curve.

[0039] Fig.12 Ti2CT at different etching times x Electrochemical performance test of @CF: (a)-(c) CV curves; (d)-(f) GCD curves.

[0040] Fig.13 Ti2CT at different etching times x Electrochemical performance test of @CF: (a) voltage and capacitance at different current densities; (b) EIS curve.

[0041] Fig.14 Ti2CT prepared by Example 1 "E-0.6V-2M-2d" of the present invention x Electrochemical performance of MXene / / Zn@CF HSC device: (a) CV curves at different scan rates; (b) constant current charge-discharge curves at different current densities; (c) 1 mA cm -2 Area specific capacitance and rate performance under current density; (d) EIS curve of HSC; (e) 1 mA cm -2 Cycling performance under current density; (f) Ti2CT x Self-discharge curves of MXene / / Zn@Cu@CF HSC.

[0042] Fig.15 Ti2CT prepared by Example 1 "E-0.6V-2M-2d" of the present invention x Application test of @CF / / Zn@Cu@CF HSC: (a) CV curves at different temperatures; (b) CV curves of a single HSC and two HSCs in series and parallel; (c) The inset shows the HSC powering the electronic clock for 12 days; (d) CV curve after the HSC powered the electronic clock for 12 days. DETAILED DESCRIPTION

[0043] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0044] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0045] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0046] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0047] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0048] In the present invention, "room temperature" is 25-30°C.

[0049] The two-dimensional vertical structure Ti2CT of the present invention x MXene electrode material (Ti2CT x @CF) preparation and zinc ion supercapacitor assembly (Ti2CT x @CF / / Zn@Cu@CF HSC) process diagram Figure 1 shown.

[0050] The internal reaction mechanism of preparing MXene in the present invention is as follows Figure 2 shown.

[0051] The experimental materials, experimental equipment and instruments used in the present invention are shown in Table 1-Table 2.

[0052] Table 1

[0053]

[0054]

[0055] Table 2

[0056]

[0057] Example 1

[0058] The present invention uses carbon fiber cloth as a matrix to prepare a two-dimensional vertical structure Ti2CT x MXene electrode materials, and the Ti2CT x The MXene electrode material is used to prepare the zinc ion supercapacitor. The specific steps are as follows:

[0059] (1) Preparation of high-purity Ti2AlC@CF by molten salt method:

[0060] After mixing carbon cloth, titanium powder and aluminum powder (titanium powder and aluminum powder molar ratio of 3:1) with molten salt (KCl:NaCl = 1:1 molar ratio), the mixture was placed in a tube furnace and heated at 1000°C for 2 hours, wherein the mass ratio of the mixed metal powder to the molten salt was 35mg:116mg. Subsequently, the product was immersed in deionized water for 30 minutes, and the surface was rinsed to remove molten salt impurities, and then placed in a drying oven at 60°C for 5 hours. After natural cooling, Ti2AlC@CF was obtained.

[0061] (2) Preparation of Ti2CTx@CF by electro-etching method:

[0062] In order to determine the appropriate voltage range for selective removal of Al in Ti2AlC, the cyclic voltammetry curve of Ti2AlC in 2M HCl aqueous electrolyte was first measured. The electrode material was prepared by chronoamperometry, the working electrode was the prepared Ti2AlC@CF electrode material, the counter electrode was an equal-area carbon cloth, and the electrolyte was an aqueous HCl solution. According to the experimental scheme in Table 3, MAX samples and 7 different specifications of Ti2CTx@CF electrode material samples were prepared. The prepared product was rinsed with deionized water and anhydrous ethanol several times to a pH of about 6, and then dried at 60°C for 5h for performance characterization.

[0063] (3) Preparation of Zn anode by electrodeposition:

[0064] The carbon fiber cloth was washed and dried with ethanol and DI water, and then treated with plasma to increase the hydrophilicity of the carbon fiber cloth. A 0.2 mol / L copper sulfate solution was prepared, and the carbon fiber cloth was used as the working electrode and the copper sheet was used as the counter electrode. The solution was immersed in the solution for 10 minutes for electrodeposition, and the excess water was taken out and dried for zinc plating. A 1.0 mol / L zinc sulfate solution was prepared, and the copper sheet was replaced with a zinc sheet, and the copper sulfate solution was replaced with a zinc sulfate solution in accordance with the copper plating method. The zinc-plated product Zn@Cu@CF was rinsed and dried.

[0065] (4) Ti2CT x Assembly of @CF / / Zn@Cu@CF HSCs:

[0066] Ti2CT was coated with 33 μm thick cellulose film. x The Zn@Cu@CF electrode was isolated from the Zn@Cu@CF electrode and a 2M ZnSO4 aqueous solution was used as the electrolyte to form the Ti2CT x @CF / / Zn@Cu@CF HSC.

[0067] Table 3

[0068]

[0069] Based on the observations under different electrochemical etching conditions, the present invention proposes a mechanism for preparing MXene by molten salt method and electro-etching method. The unetched precursor Ti2AlC is marked as "MAX", and the MXene materials with different etching voltages, etching solution concentrations and etching times are marked and named accordingly, such as the sample electro-etched in +0.6V 2M HCl for 1d is marked as "E-0.6V-2M-1d", and the working electrodes after etching for 2d and 4d are marked as "E-0.6V-2M-2d" and "E-0.6V-2M-4d", respectively.

[0070] Figure 3 SEM images and EDS images of MAX and samples etched for different times at a voltage of 0.6 V and a concentration of 2 M HCl are shown: (a) MAX; (b) sample E-0.6V-2M-1d (2000 times); (c) sample E-0.6V-2M-2d (2000 times); (d) sample E-0.6V-2M-2d (4000 times); (e) sample E-0.6V-2M-2d (60000 times); (f) sample E-0.6V-2M-4d (2000 times); (g) full spectrum of E-0.6V-2M-2d; (g1)-(g3) are EDS element mapping images of O, C, and Ti of E-0.6V-2M-2d, respectively.

[0071] Figure 3(a) shows that after the in-situ growth of Ti2AlC MAX on the CF surface in the “MAX” sample, the CF surface becomes denser and rougher, but the fiber structure is well maintained. The fiber diameter of sample “E-0.6V-2M-1d” did not change after electro-etching, but some voids left by the detachment of some substances were observed on its surface. According to the data in Table 4, the Ti / Al ratio increased from 1.9 to 5.58, which indicates that the detached material is Al etched from the precursor MAX phase. However, the Ti2CT x The content is too small to be detected by XRD.

[0072] Figure 3 (c)-(d) show 2000x and 4000x SEM images of the sample “E-0.6V-2M-2d”, showing spike-like two-dimensional Ti2CT growing vertically on the carbon rod. x MXene, with a loose surface, Al is basically etched away from the precursor Ti2AlC MAX phase, and the vertically aligned growth structure of MXene is more obvious. x @CF high magnification SEM image shows that the surface of the sample is composed of many irregular adjacent nanosheets that coalesce to form larger Ti2CT x MXene nanosheets, with a lateral diameter of approximately 1.68 μm, have a large specific surface area that provides a large number of attachment sites, which is beneficial for the embedding / de-embedding of ions, thereby improving the electrochemical performance of the device.

[0073] Figure 3 (f) shows that the fiber diameter of sample “E-0.6V-2M-4d” becomes thinner, and the two-dimensional layered MXene on the surface falls off, and the EDS element content analysis table in Table 4 and Figure 5 (b) XRD patterns further confirmed that almost no Al was detected in sample “E-0.6V-2M-4d”, while the atomic content of Ti element also decreased by 53%, indicating that most of the Al and Ti in Ti2AlC were etched into carbide-derived carbon (CDC). Figure 3 (g)-(g3) are the element mapping diagrams of the sample “E-0.6V-2M-2d”, which reflect that C, O, and Ti are evenly distributed on the carbon fiber. It can be seen from the Ti element mapping diagram that the Ti content is very high, which may be due to a small amount of TiC attached to the surface of MXene.

[0074] Each sample was scanned at least three times by an energy spectrometer, and the average atomic content percentage is shown in Table 4. No other impurity ions were detected in the precursor Ti2AlC, and its Ti / Al atomic weight ratio was 1.90. The Ti / Al atomic weight ratio of the product obtained after 1d of etching was higher than MAX, further confirming that electro-etching can remove the Al layer in MAX. After 2d of electro-etching, Al was almost completely etched away, which further proves the effectiveness of the process.

[0075] Table 4

[0076]

[0077] Figure 4 Ti2CT x Elastic recovery performance of @CF electrode material (E-0.6V-2M-2d): (a) C-shaped Ti2CT x @CF electrode material; (b) curved S-shaped Ti2CT x @CF electrode material; (c) unfolded Ti2CT x @CF electrode material. Figure 4 Clearly shows the prepared Ti2CT x @CF electrode has excellent flexibility and can be bent into C-shape or S-shape. Figure 4 (c) shows the Ti2CT after multiple bending. x @CF electrode can still fully recover to its original shape, showing excellent elastic recovery performance. Compared with LiF-HCl chemical etching, the mechanism of electrochemical etching in HCl electrolyte is very similar to that of LiF-HCl liquid phase etching.

[0078] After being treated with different voltages and electrolyte concentrations, the SEM images of the samples are roughly similar. When the etching time is 2d and the electrolyte concentration is 2M, the sample "E-0.4V-2M-2d" treated at 0.4V voltage has almost no change; while the sample "E-0.6V-2M-2d" treated at 0.6V voltage has a layered structure; when the voltage is increased to 0.8V, due to the excessive voltage, the MAX layer of the sample "E-0.8V-2M-2d" is easily etched and falls off quickly. When the etching voltage is 0.6V and the electrolyte concentration is 1M, the sample needs 4 days to be completely etched, but MXene easily falls off the carbon fiber surface after long-term etching; when the electrolyte concentration is 2M, the sample "E-0.6V-2M-2d" can be completely converted into MXene in just 2 days; however, when the electrolyte concentration is 4M, the sample "E-0.6V-4M-2d" is over-etched like under the voltage condition of 0.8V.

[0079] XRD, FT-IR, and XPS spectrum analysis of MAX and MXene:

[0080] The elemental composition of MAX grown on the carbon fiber surface was analyzed by XRD spectrum. Figure 5 (a) shows that MAX is composed of Ti2AlC and TiC, while the peaks of carbon fiber are relatively weak. The diffraction peaks at 2θ = 13.0°, 33.8°, 39.3°, and 53.3° correspond to the (002), (100), (104), and (106) planes of Ti2AlC. After electro-etching, most of the diffraction peaks of Ti2AlC MAX almost disappeared, indicating that the Al layer has been completely removed. At 2θ = 8.7°, the diffraction peaks of Ti2CT x The diffraction peaks are shown. Since most Ti2CT x Since the orientation of the sheet cannot meet the conditions for generating diffraction signals, the Ti2CT x The (002) phase diffraction peak is very weak.

[0081] like Figure 5 (b) shows the XRD pattern of the sample obtained at room temperature (30°C). In the sample “E-0.6V-2M-1d”, no Ti2CT x The characteristic peaks of MXene are shown in Figure 2, while the Ti2AlC peaks at 13.0° and 39.3° are obvious, indicating that Al is not completely removed after 1 day of etching. In order to further explore the room temperature etching process, the reaction time was extended from 1 day to 4 days of different etching times. After 2 days of etching, the Ti2AlC peak intensity in the sample "E-0.6V-2M-2d" decreased, and Ti2CT x The disappearance of the high-intensity peak at 39.3° and the shift of the characteristic peak at 13° to 8.7° indicate that Ti2AlC MAX undergoes chemical exfoliation and is converted into Ti2CT after 2d of etching. x MXene. After 4 days of etching, Ti2CT in sample “E-0.6V-2M-4d” x The characteristic peak at 8.7° disappears, indicating that the extension of etching time will affect the composition of the sample. Among them, the morphology, structure and composition of the sample "E-0.6V-2M-2d" are the best, so FT-IR and XPS test analysis were carried out.

[0082] Figure 6 Ti2CT x @CF(E-0.6V-2M-2d) infrared spectrum. Figure 6 As shown, in HCl aqueous electrolyte, Al element was initially removed from Ti2AlC to form MXene (Ti2CT) with -Cl, -O, and -OH surface termination groups. x). Functional groups affect the properties of MXenes. The introduction of HCl into -Cl surface terminal groups improves the performance of Ti2CT x This improvement in the electrochemical performance of MXene can be attributed to the increase in the interlayer spacing of MXene, which facilitates the insertion of ions.

[0083] Figure 7 XPS spectra of sample “E-0.6V-2M-2d”: (a) overall spectrum of sample “E-0.6V-2M-2d”, (b) C 1s spectrum; (c) Ti 2p spectrum; (d) O 1s spectrum.

[0084] Figure 7 (a) shows the full spectrum of MXene materials, which contains C, Ti, and O elements, indicating that no other impurities are produced when MXene is used as an electrode reaction. Figure 7 As shown in (b), the peak with a binding energy of 288.64 eV represents a C=O bond, the peak with a binding energy of 284.80 eV represents a CC bond, and the peak with a binding energy of 281.70 eV represents a C-Ti bond. Figure 7 As shown in (c), the Ti 2p peak can be fitted by two symmetrical peaks located at 454.90 eV and 460.96 eV, which correspond to the C-Ti bond. The characteristic peaks of Ti 2p at the binding energies of 458.62 eV and 464.24 eV correspond to the Ti-O bond. Figure 7 (d) shows the spectrum of O1s, where the peak at 531.53 eV represents C-Ti-(OH)x, and the binding energy at 529.98 eV corresponds to C-Ti-O, revealing the bonding mechanism between the MXene layer and the carbon fiber. Figure 7 In (c)-(d), the formation of Ti-O bonds confirms the selective removal of the Al layer. As the reaction continues, the formed Ti2C remains as part of the working electrode, while the Ti atoms are etched, resulting in the formation of a small amount of CDCs. Finally, the peaks of CC and CO observed in the C1s spectrum are very consistent with the characteristics of CDCs, indicating the occurrence of over-etching. These analytical results provide a deep understanding of the structural evolution of MXene materials during electrode reactions, which helps to explain their electrochemical properties and energy storage mechanisms.

[0085] Effect verification:

[0086] Ti2CT x @CF / / Zn@Cu@CF HSC electrochemical performance test:

[0087] In order to test the electrochemical performance of the electrode materials, Ti2CT x Ti2CT@CF material, zinc electrode and 2M ZnSO4 electrolyte were assembledx @CF / / Zn@Cu@CF HSC was prepared and its electrochemical performance was tested. The effects of different etching solution concentrations, etching voltages and etching times on its electrochemical performance were systematically studied, and the best etching conditions were selected through process optimization.

[0088] 1. Effect of different etching voltages on Ti2CT x Effect of @CF / / Zn@Cu@CF on the electrochemical performance of HSC

[0089] Figure 8 Electrochemical performance test of samples under different etching voltages: (a)-(c) CV curves; (d)-(f) GCD curves.

[0090] like Figure 8 As shown in (a)-(c), cyclic voltammetry curves were tested on HSC assembled with electrode materials obtained at three etching voltages. Judging from the closed area enclosed by the cyclic voltammetry curves, the CV area of ​​HSC shows a trend of first increasing and then decreasing with the increase of etching voltage. When the etching voltage increases to 0.6V, its capacitance reaches its maximum value. This is because the precursor MXene decomposes under the voltage etching of 0.6V, releasing active sites, which is beneficial to increase the capacitance. As the scan rate increases, there is no obvious deformation of the CV curve, indicating that the device has excellent rate stability. However, when the voltage increases to 0.8V, the capacitance of HSC drops sharply. From Figure 3 From the SEM image of (f), it can be seen that MXene nanosheets are easily detached from CF after high voltage etching, which may be the reason for the decrease in the electrochemical performance of HSC. Figure 8 (d)-(f) show the charge and discharge curves of HSC obtained by charge and discharge tests at different current densities. These GCD curves are triangular in shape, while the GCD curve of HSC assembled with sample "E-0.6V-2M-2d" is closer to an isosceles triangle with no obvious voltage drop. Combining the data in Table 5, and using formulas (1-1) and (1-2), the capacitance of HSC at different voltages is calculated. It is worth noting that the HSC assembled with sample "E-0.6V-2M-2d" exhibits the largest area specific capacitance, which indicates that having a wide spacing MXene helps to achieve faster charge storage and release, thereby having better electrochemical performance.

[0091]

[0092] In formula (1-1):

[0093] C: specific capacitance, in mF;

[0094] I: current, in mA;

[0095] Δt: discharge time, in h;

[0096] ΔV: potential window, unit is V.

[0097]

[0098] In formula (1-2):

[0099] Cs is the area specific capacitance, in mF / cm 2 ;

[0100] I: current, in mA;

[0101] Δt: discharge time, in h;

[0102] ΔV: potential window, unit is V;

[0103] S: electrode area, in cm 2 .

[0104] Table 5 is a comparison of the area specific capacitance values ​​of hybrid supercapacitors under different etching voltages.

[0105] Table 5

[0106]

[0107] Fig. 9 Electrochemical performance test of samples under different etching voltages: (a) voltage-capacitance at different current densities; (b) EIS curve. Fig. 9 (a) shows the current density from 1 to 6 mA cm -2 The area specific capacitance of HSC at different etching voltages is shown as the scan rate increases. It is worth noting that the area specific capacitance at an etching voltage of 0.6 V is much higher than that of the other two samples. When the scan rate increases by 6 times, almost 70% of the capacitance is retained, which indicates that the capacitor has good rate performance. Fig. 9 (b) Demonstrates excellent charge transfer and ion transport properties. The EIS curve confirms that the HSC assembled with sample "E-0.6V-2M-2d" has a low charge transfer resistance of 1.21Ω. By comparing the EIS graphs, it can be seen that the surface of the MXene material is conducive to charge transfer, so the charge transfer impedance is relatively low, and there is no obvious semicircle in the high-frequency region. The equivalent resistance of sample "E-0.6V-2M-2d" is the smallest, mainly because at an appropriate voltage, the expansion of the MXene interlayer spacing makes the transmission and diffusion of electrolyte ions more convenient.

[0108] 2. Effect of different etching solution concentrations on Ti2CT x Effect of @CF / / Zn@Cu@CF on the electrochemical performance of HSC

[0109] Fig.10 Electrochemical performance test of samples under different etching solution concentrations: (a)-(c) CV curves; (d)-(f) GCD curves.

[0110] like Fig.10 As shown in (a)-(c), the area enclosed by the cyclic voltammetry curve of HSC increases first and then decreases with the increase of the molar concentration of HCl electrolyte, and the CV curve area is the largest when the concentration is 2M. Fig.10 (d)-(f) show the charge and discharge curves of HSC at different current densities. Table 6 calculates the capacitance of different samples by combining the GCD curve and using formulas (1-1) and (1-2).

[0111] Table 6 is a comparison of the area specific capacitance values ​​of the hybrid supercapacitors at different etching solution concentrations.

[0112] Table 6

[0113]

[0114] Fig.11 Electrochemical performance test of samples with different etching solution concentrations: (a) voltage and capacitance at different current densities; (b) EIS curve.

[0115] Fig.11 (a) shows the hybrid supercapacitors assembled from electrode materials prepared at different etching solution concentrations at current densities ranging from 1 to 6 mA cm -2 The obtained area specific capacitance shows that the area specific capacitance of sample “E-0.6V-2M-2d” is much higher than that of the other two samples. -2 At a current density of 1.3 Å, the area specific capacitance of the HSC assembled by the sample “E-0.6V-1M-2d” is 60.00 mF cm -2 As the concentration of the etching solution increases, the capacity of the capacitor gradually increases. When the etching solution concentration is 2M, the area specific capacitance reaches 328.12mF cm -2 As the etching solution concentration further increases to 4M, it can be seen that the area specific capacitance decreases rapidly, but the rate stability is good.

[0116] Fig.11 (b) is the EIS curve of the hybrid supercapacitor assembled with electrode materials under different etching solution concentrations. The impedance diagrams of sample "E-0.6V-1M-2d" and sample "MAX" are almost the same, further indicating that the electrolyte with a concentration of 1M has almost no etching effect on MAX. In the low-frequency region, the EIS curve of the hybrid supercapacitor assembled with sample "E-0.6V-2M-2d" has a larger slope than that of sample "E-0.6V-4M-2d", which is closer to the ideal capacitance behavior.

[0117] 3. Effect of different etching time on Ti2CT x Effect of @CF / / Zn@Cu@CF on the electrochemical performance of HSC

[0118] Fig.12 Electrochemical performance tests of samples at different etching times: (a)-(c) CV curves; (d)-(f) GCD curves.

[0119] like Fig.12 As shown in (a)-(c), the area of ​​the CV curve increases first and then decreases with the increase of etching time, and there is no obvious shift in the CV curve when the scanning rate increases.

[0120] From the closed area enclosed by the cyclic voltammetry curve, when the etching time increases to 2d, the area enclosed by the CV curve of HSC reaches the maximum. As the etching time increases to 4d, the area enclosed by the CV curve of HSC decreases sharply. Fig.12 (d)-(f) show the charge and discharge curves of HSC assembled with electrode materials prepared with different etching times, all of which are similar to isosceles triangles and have no obvious voltage drop. As shown in Table 7, the capacitance of HSC is calculated by formula (1-1) and (1-2) combined with the GCD curve.

[0121] Table 7 is a comparison of the area specific capacitance values ​​of the hybrid supercapacitors at different etching times.

[0122] Table 7

[0123]

[0124]

[0125] Fig.13 Electrochemical performance test of samples at different etching times: (a) voltage-capacitance at different current densities; (b) EIS curve.

[0126] Fig.13 (a) shows the current density from 1 to 6 mA cm -2 The area specific capacitance of the hybrid supercapacitor under different etching times is within the range of . It is worth noting that the area specific capacitance of the sample “E-0.6V-2M-2d” is much higher than that of the other two samples. The specific values ​​can be seen in Table 7. -2 At a current density of 1.3 Å, the area specific capacitance of the HSC assembled from the sample after 1 d etching time is 179.23 mF cm -2 As the etching time increases, the capacity of HSC gradually increases. When the etching time increases to 2 days, the area specific capacitance of HSC assembled with electrode materials reaches 328.12 mF cm -2, which is mainly attributed to the increase in the interlayer spacing between MXene nanosheets, thereby accelerating the charge transfer rate. However, as the etching time further increased to 4d, the MXene nanosheets fell off the carbon fibers, causing the HSC area specific capacitance to drop rapidly. When the current density increased by 6 times, the capacitance of the HSC assembled with the electrode materials of sample "E-0.6V-2M-1d", sample "E-0.6V-2M-2d" and sample "E-0.6V-2M-4d" retained 75.3%, 70% and 76.1%, respectively, indicating that the HSC has excellent rate stability and excellent rate performance.

[0127] Fig.13 (b) shows the EIS curves of hybrid supercapacitors assembled with electrode materials after different electro-etching times. In the high-frequency region, no obvious semicircle appears, which indicates that the electron transfer speed on the two electrode surfaces is very fast and the charge transfer impedance is relatively low. In the low-frequency region, a nearly vertical oblique line segment is presented. It is worth noting that the slope of the sample "E-0.6V-2M-4d" is the largest, which may be due to the performance characteristics of the carbide surface produced by excessive electro-etching.

[0128] 4. Ti2CT prepared under optimal conditions x Electrochemical performance test of MXene / / Zn@CF HSC

[0129] In summary, the zinc ion hybrid supercapacitor assembled with the electrode material of sample "E-0.6V-2M-2d" exhibits the best electrochemical performance.

[0130] Fig.14 Ti2CT x Electrochemical performance of MXene / / Zn@CF HSC device: (a) CV curves at different scan rates; (b) constant current charge-discharge curves at different current densities; (c) 1 mA cm -2 Area specific capacitance and rate performance under current density; (d) EIS curve of HSC; (e) 1 mA cm -2 Cycling performance under current density; (f) Ti2CT x Self-discharge curve of MXene / / Zn@Cu@CFHSC.

[0131] like Fig.14 As shown in (a), during the CV measurement, the peak current output of the anodic and cathodic curves and the area under the curve increase with the increase of the scan rate. When the scan rate increases from 10 to 300 mV s -1 The area under the curve becomes larger when . No obvious redox peak appears, indicating that the charge / discharge rate is relatively constant during the entire scan.

[0132] Fig.14 (b) shows the current density from 1 mA cm -2 to 6mA cm -2 The almost symmetrical triangular curve shows that there is a stable voltage window at different current densities. The current density is 1 mA cm -2 There is little ohmic drop (IR, 0.031V) when HSC is used, indicating that HSC has a certain resistance, which reveals the typical capacitive charge storage behavior. Fig.14 (c) shows that the capacitance ranges from 330 to 232 mF cm -2 , at 0.497 mW cm -2 At a power density of 45.3 μWh cm -2 With a 6-fold increase in scan rate, the HSC retains almost 70.4% of its capacitance, demonstrating the excellent rate stability of the fabricated device.

[0133] Fig.14 (d) shows excellent charge transfer and ion transport properties, with a very steep slope at low frequency and the curve graph being almost parallel to the imaginary part. The EIS curve confirms a low charge transfer resistance of 1.21Ω, indicating that the fabricated HSC array has good capacitive performance. Fig.14 (e) shows the -2 After 2000 cycles at the same current density, the capacity retention rate of HSC was 96.16%, demonstrating its excellent cycle stability. 2+ The ions are reduced to Zn atoms and adhere to the surface of the Zn anode, rather than forming ion accumulation on the anode, which greatly weakens the internal electrostatic field between the electrodes. These uncharged zinc atoms will not transfer to the MXene cathode under open circuit conditions. As for the self-discharge curve of HSC, it is as follows Fig.14 As shown in (f), its self-discharge rate is 0.78mV h -1 .

[0134] Fig.15 Ti2CT x Application test of @CF / / Zn@Cu@CF HSC: (a) CV curves at different temperatures; (b) CV curves of a single HSC and two HSCs in series and parallel; (c) The inset shows that the HSC powers the electronic clock for 12 days; (d) CV curve after the HSC powers the electronic clock for 12 days.

[0135] exist Fig.15In (a), the CV curves of HSC at different temperatures are tested. The results show that within the temperature range of 0℃~50℃, as the temperature increases, the energy storage effect gradually increases, but polarization occurs at 50℃. Fig.15 (b) shows the CV curves of a single HSC and two HSCs in series and parallel. At the same scan rate, the series or parallel connection shows double the output voltage / current. Fig.15 (c) The continuous output voltage under load was tested, especially two zinc ion HSCs connected in series as the power source of the electronic clock, and the electrode voltage under load was observed. Even under load, the HSC can maintain a stable voltage output and can provide power for up to 12 days. Fig.15 In (d), after the electronic clock was powered for 12 days, the voltammetric characteristic curve of the single electrode showed a voltage between 50 and 300 mV cm -2 At a scan rate of , the area of ​​the CV curve decreases after 12 days of power supply, showing a shuttle shape, and no deformation occurs with the increase of the scan rate, which verifies that HSC has better stable voltage output capability.

[0136] The present invention uses a constant voltage to etch the Ti2AlC MAX phase. The electrochemical etching method does not involve any F + , eliminating the harm to the environment and human body caused by traditional HF etching, and producing Ti2CT with only -Cl, -O and -OH end groups X Among them, Ti2CT X The 2D nature of the oriented vertical arrangement is extremely beneficial to supercapacitors, enhancing the mechanical stability and shortening the ion diffusion path between positive and negative ions, accelerating ion transport.

[0137] The carbon fiber is not only a self-supporting independent flexible substrate in the synthesis process of Ti2AlC MXene phase, but also can provide a carbon source. x The CF electrode has excellent area capacitance and cycling stability in ZnSO4 aqueous electrolyte at a power density of 0.493 mW / cm 2 Under the condition of 45.3μWh / cm 2 High energy density. Two supercapacitors charged in series can light up a red LED (2.0V, 15mA) for 8 minutes and an electronic clock for 12 days.

[0138] The present invention successfully prepared self-supporting and vertically aligned Ti2CT by electro-etching method. x @CF electrode material, which has excellent fast electron transfer channels and is suitable for zinc ion hybrid supercapacitor applications.

[0139] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A two-dimensional vertical structure Ti2CT x The method for preparing MXene electrode material is characterized in that: The following steps are involved: After mixing the mixed metal powder, molten salt and carbon cloth, the carbon cloth-based MAX material, i.e. Ti2AlC@CF, is obtained by melting. The Ti2AlC@CF was electroetched to obtain a two-dimensional vertical structure Ti2CT x MXene electrode materials; The mixed metal powder is a mixed metal powder composed of Ti powder and Al powder; The etching voltage of the electric etching is 0.4-0.8V, the etching solution is HCl aqueous solution, the etching solution concentration is 1-4M, and the etching time is 1-4d.

2. The preparation method according to claim 1, characterized in that: The temperature of the melting treatment is 1000° C. and the time is 2 hours.

3. The preparation method according to claim 1, characterized in that: The etching voltage is 0.6 V, the etching solution is HCl aqueous solution, the etching solution concentration is 2 M, and the etching time is 2 d.

4. The preparation method according to claim 1, characterized in that: The melting process also includes washing and drying steps.

5. The two-dimensional vertical structure Ti2CT according to claim 1 x Application of MXene electrode materials as supercapacitor electrode materials.

6. The use according to claim 5, characterized in that: The supercapacitor is a zinc ion supercapacitor.

7. The use according to claim 6, characterized in that: The electrolyte of the zinc ion supercapacitor is a ZnSO4 aqueous solution.

8. A supercapacitor, characterized in that: Using the two-dimensional vertical structure Ti2CT according to claim 1 x MXene electrode materials are used as electrode materials.

9. The supercapacitor according to claim 8, characterized in that: The supercapacitor is a zinc ion supercapacitor, and the counter electrode is Zn@Cu@CF; the preparation method of Zn@Cu@CF comprises the following steps: A first electrodeposition is performed using carbon cloth as a working electrode, a copper sheet as a counter electrode, and a copper sulfate solution as a plating solution, and a second electrodeposition is performed using the obtained electrodeposited material as a working electrode, a zinc sheet as a counter electrode, and a zinc sulfate solution as a plating solution to obtain the Zn@Cu@CF.